Developing an Effective Regulatory Regime for E-Commerce in the Southern African Development Community (SADC): Proposed Solutions - Vongai Chimeri; Tapiwa Shumba (Potchefstroom Electronic Law Journal)
The outbreak of the Coronavirus Pandemic (COVID-19) in 2019 has accelerated digital transformations particularly in the area of e-commerce. The imposition of public health-related lockdowns limited physical movement and increased the demand and use of e-commerce worldwide. While other businesses in developed countries saw the outbreak of the COVID-19 as an opportunity to expand their digital markets, in Africa, particularly in the Southern African Development Community (SADC) it highlighted the need to bridge the digital divide both within and across the region, that continues to hinder greater participation in e-commerce activities. A regulatory framework that harmonises e-commerce laws to enhance legal certainty and predictability is considered important to enable the development of e-commerce. Although the SADC Model Law on Electronic Transactions and Electronic Commerce (SADC Model Law) was adopted with the aim of harmonising e-commerce laws in the SADC region, the regulation of e-commerce in the SADC remains inadequate, fragmented and in some instances outdated. This article examines the regulation of e-commerce in the SADC and concludes that it does not support the development of e-commerce in the region. It identifies some challenges that are inhibiting the development of e-commerce and offers some solutions that might help enable the development of e-commerce in the SADC.